PERBEDAAN KINERJA DAN NILAI PERUSAHAAN SEBELUM DAN SETELAH PERGANTIAN CHIEF EXECUTIVE OFFICER - Prasantia Noor, I Ketut; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine differences in financial performance before and after the turn of the CEO and the market value before and after the change of CEO. This research was conducted in a manufacturing company doing CEO turnover and listed in Indonesia Stock Exchange 2010-2014. The number of samples in this study were 30 companies using purposive sampling. Data analysis technique used is a different test. Based on the analysis found that there are differences in the performance and the value of the company before and after the change of CEO. This means, the new CEO did income decreasing, even big bath in the first year he took office. Poor performance is delegated to the CEO who long to reduce earnings at the beginning of the new CEO took office. With the profit decline would certainly increase the possibility of obtaining a higher profit in the next period.
Keywords: CEO, the company' s performance, the value of the company